Location-Aware Type Ahead Search on Spatial Databases: Semantics and Efficiency - Roy, Senjuti Basu; Chakrabarti, Kaushik (ACM SIGMOD Conference, 2011)
Users often search spatial databases like yellow page data using keywords to ﬁnd businesses near their current location. Such searches are increasingly being performed from mobile devices. Typing the entire query is cumbersome and prone to errors, especially from mobile phones. We address this problem by introducing type-ahead search functionality on spatial databases. Like keyword search on spatial data, type-ahead search needs to be location-aware, i.e., with every letter being typed, it needs to return spatial objects whose names (or descriptions) are valid completions of the query string typed so far, and which rank highest in terms of proximity to the user’s location and other static scores. Existing solutions for type-ahead search cannot be used directly as they are not location-aware. We show that a straight-forward combination of existing techniques for performing type-ahead search with those for performing proximity search perform poorly. We propose a formal model for query processing cost and develop novel techniques that optimize that cost. Our empirical evaluations on real and synthetic datasets demonstrate the eﬀectiveness of our techniques. To the best of our knowledge, this is the ﬁrst work on location-aware type-ahead search.